A NILAI MORAL PADA CERPEN WIRO SELEDRI KARYA GM SUDARTA - Farhat Faqih (Universitas Muhammadiyah Surabaya, 2025)
The focus of this research is on the category of moral values ​​in the short story Wiro Seledri by GM Sudarta as stated by Nurgiyantoro. The aim of this research is to see to what extent the short story Wiro Seledri contains categories of moral values, including the relationship between humans and themselves, the relationship between humans and the environment and the natural surroundings, and the relationship between humans and God. The type of method in this research uses descriptive qualitative, while the data collection technique uses library research by reading object texts, observing, classifying, reducing and interpreting the data. The theory used in this research is Nurgiyantoro's theory of moral values ​​which is categorized into three types, namely the relationship between humans and themselves, the relationship between humans and the environment and the natural surroundings, and the relationship between humans and God. The findings from this research are that there are moral values ​​that are classified based on problem categories. First, 5 data were found in the category of human relations with themselves in the form of quotations. Second, 4 data were found in the category of human relations with the environment and the natural surroundings in the form of quotations. And finally, data was found in the category of human relationship with God, totaling 4 data with the same form.